A unified work breakdown structure-based framework for building asset management. Issue 4 (14th August 2020) - Al-Kasasbeh, Maha; Abudayyeh, Osama; Liu, Hexu
Abstract : Purpose: Asset inventory is an essential part of any building asset management system and is needed by such functions as condition assessment and deterioration prediction. Previous studies in asset management systems have suggested the use of one of the many standard construction classification systems, such as UniFormat or MasterFormat, in achieving the goals of asset management. However, each classification system has its unique features, and it has been developed for different purposes and may not necessarily be directly adaptable to asset management. A proper classification system is thus needed to achieve the goals of building asset management effectively. Such a system must take into consideration the objectives and functions of asset management. Therefore, the purpose of this paper is to establish a unified work breakdown structure (WBS)-based framework for building asset inventory. Design/methodology/approach: The WBS-based framework aims to cover the entire lifecycle of an asset so as to provide the unified classification system for asset inventory. The proposed framework is developed based on appropriate building standards. Also, comprehensive levels of details are included for space functions and locations for all assets in any type of building. Furthermore, this framework takes into consideration utilities in any kind of building project. As such, the WBS-based framework proposed in this research endeavor provides the basis for effective asset management. An educational building case study is presented and discussed to demonstrate the effectiveness of the proposed framework for asset management. Findings: The unified WBS-based framework for building asset management effectively classifies asset inventories and facilitates decision-making in asset management during the lifecycle of an asset. Originality/value: This research synthesizes a unified WBS-based framework for building asset management, which allows for a more effective lifecycle building asset management.